Model Dakwah Inklusif Persatuan Islam Tionghoa Indonesia (Piti): Integrasi Islam, Budaya Tionghoa Dan Pelayanan Sosial - Syahrizal; Suprapto (Mudabbir: Jurnal Manajemen Dakwah, 2025)
This study examines the Islamic missionary movement of the Indonesian Chinese Islamic Association (PITI). This study aims to analyze how PITI integrates Islamic values ??with Chinese cultural identity, implements social programs that benefit the community, and fosters the community through education and spiritual guidance. The research method used is descriptive qualitative, with data collection techniques through literature studies. The results of the study indicate that PITI carries out cultural missionary work by integrating religious practices and ethnic identity, social missionary work through community service programs, economic empowerment, and assistance for Chinese converts, and fostering the community through religious studies, spiritual guidance, and skills training. The PITI missionary movement proves that an integrated missionary approach between social and spiritual aspects can improve welfare, strengthen social integration, and facilitate a comprehensive understanding of religion. These findings provide an important contribution to the study of missionary work in minority communities and models of inclusive socio-religious movements in Indonesia.